2013
DOI: 10.1002/dc.23025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the cervista and hybrid capture 2 methods in detecting high‐risk human papillomavirus in cervical lesions

Abstract: High-risk human papillomavirus (HR HPV) testing is important for the follow-up of patients with cytological abnormalities. This study was undertaken to compare the clinical value of the Cervista and hybrid capture 2 (HC2) tests for detection of HR HPV in cervical lesions. Overall 439 cervical specimens with abnormal cytology and 22 normal cervical specimens were subjected to the Cervista and HC2 tests. HPV positivity and its predictive value for high-grade cervical lesions were assessed. The Cervista and HC2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
2
7
2
Order By: Relevance
“…Furthermore, discrepancy analysis revealed a high false positive rate for Cervista using the currently approved cut-off values (n = 56 for Cervista versus n = 3 for HC2; Table 5). This result, however, is not in line with previous studies demonstrating a tendency of a lower or no difference in the HR HPV prevalence rate for Cervista in comparison to HC2 in women with NILM cytology [12]-[17]. This disagreement with previous reports might, however reflect differences in study design [12],[13],[16],[17], age range of participants [12],[13],[15]-[17] or overall HR HPV prevalence rates [14].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Furthermore, discrepancy analysis revealed a high false positive rate for Cervista using the currently approved cut-off values (n = 56 for Cervista versus n = 3 for HC2; Table 5). This result, however, is not in line with previous studies demonstrating a tendency of a lower or no difference in the HR HPV prevalence rate for Cervista in comparison to HC2 in women with NILM cytology [12]-[17]. This disagreement with previous reports might, however reflect differences in study design [12],[13],[16],[17], age range of participants [12],[13],[15]-[17] or overall HR HPV prevalence rates [14].…”
Section: Discussioncontrasting
confidence: 99%
“…Although relative specificity was better for the Cervista HPV HR test (15.7%) than for HC2 (9.8%), the difference was not significant (p value = 0.14), which is supported by the results obtained from our ratio analysis. Our findings confirm the results of previous publications, which compared the performances of the Cervista HPV HR test and the HC2 tests and showed no significant differences in sensitivities detecting histologically confirmed high grade lesions (CIN2+ or CIN3+) [12],[16],[17]. These studies also demonstrated differences in specificities in favour for the Cervista® HPV HR test, however only Belinson et al was able to show that this difference was of statistical significance [17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is advocated that the interval for repeat screening can be extended to 5 years due to the increased sensitivity with this co-testing. The HR-HPV testing may be useful for management of patients with abnormal cervical smears (Tao et al, 2013). It has been shown that a single HPV test at around 35 years of age is the most cost-effective intervention in reducing the burden of cervical cancer in countries with low or no screening coverage (Goldie et al, 2005).…”
Section: Discussionmentioning
confidence: 99%